2004
DOI: 10.1023/b:qure.0000015296.14717.e7
|View full text |Cite
|
Sign up to set email alerts
|

Subjective quality of life and positive appraisal of care among Japanese family caregivers of older adults

Abstract: Most family caregiving research has portrayed caregiving as a negative life experience for caregivers, but a broader perspective is necessary to examine its impact on the caregiver quality of life (QL). The role that positive appraisal of care plays in the caregiving experience among Japanese families of older adults was examined in relation to the caregiver's subjective QL. Positive as well as negative appraisal of care was measured by a newly developed multi-dimensional scale, which included the domains of '… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…In the existing literature, researchers found a pattern: the lower the patient's symptom level, the higher the QOL of the FC [45,46]. Researchers also suggested that if FCs know what to expect when they provides end-of-life care at home, their stress levels would decrease, thereby giving them a higher level of confidence in caregiving and, subsequently, a better QOL [46,47]. In addition, as FCs perceive the degree to which caregiving has changed their various life domains (such as daily schedule, health, family support, and financial sufficiency in meeting the patient's medical care needs) for the worse, their subjective caregiving burden increases and their QOL decreases [12,20,48,49].…”
Section: Discussionmentioning
confidence: 93%
“…In the existing literature, researchers found a pattern: the lower the patient's symptom level, the higher the QOL of the FC [45,46]. Researchers also suggested that if FCs know what to expect when they provides end-of-life care at home, their stress levels would decrease, thereby giving them a higher level of confidence in caregiving and, subsequently, a better QOL [46,47]. In addition, as FCs perceive the degree to which caregiving has changed their various life domains (such as daily schedule, health, family support, and financial sufficiency in meeting the patient's medical care needs) for the worse, their subjective caregiving burden increases and their QOL decreases [12,20,48,49].…”
Section: Discussionmentioning
confidence: 93%
“…We therefore did not ask about satisfaction, mastery, or cognitive reappraisal-aspects of caregiving that reflect the positive side of caregiving. An increasing body of literature 27,28 suggests that caregiving may lead to positive emotions when the caregiver finds new meaning in the experience (cognitive reappraisal) and/or experiences satisfaction in mastering the complex tasks of caregiving. Respondents answered each of the items using a 5-point scale that asked either the extent to which the statement was true (never to nearly always) or the extent to which the caregiver agreed (strongly agree to strongly disagree).…”
Section: Methodsmentioning
confidence: 99%
“…However, the consequences of caregiving do not have to be necessarily negative. Japanese researchers Noriko et al (2004) have pointed out both positive and negative aspects of caregiving. They used a scale of positive assessments and statements divided into the categories of relationship satisfaction, role confidence and normative fulfilment.…”
Section: Introductionmentioning
confidence: 99%